2013
DOI: 10.1039/c2lc41000a
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic confinement of axonal growth for dynamically configurable neural networks

Abstract: Axons in the developing nervous system are directed via guidance cues, whose expression varies both spatially and temporally, to create functional neural circuits. Existing methods to create patterns of neural connectivity in vitro use only static geometries, and are unable to dynamically alter the guidance cues imparted on the cells. We introduce the use of AC electrokinetics to dynamically control axonal growth in cultured rat hippocampal neurons. We find that the application of modest voltages at frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…In short, microfluidic and electric fields can be combined to control neuronal connectivity [127]. In this line, the next section deals with the control of neuronal architectures combined with the implementation of recording/stimulation electronics.…”
Section: Polarity Axon-locks At Neuronal Population Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, microfluidic and electric fields can be combined to control neuronal connectivity [127]. In this line, the next section deals with the control of neuronal architectures combined with the implementation of recording/stimulation electronics.…”
Section: Polarity Axon-locks At Neuronal Population Levelsmentioning
confidence: 99%
“…Adhesive patterns in the millimeter range have also been employed to create another type of axonal diodes: in the work of Feinerman et al [126], the 50 lm wide restricted contact zones joining millimeter sized triangles induced a preferential unidirectional crossing of the axons toward the tip of these geometric shapes. Dielectrophoresis was also used to dynamically control axonal growth through electrical axon-lock [127]. By a ''Stop and go'' electrokinetic effect on axonal growth, configurable and directional mature neural networks between up to three different neuronal compartments were implemented (Fig.…”
Section: Polarity Axon-locks At Neuronal Population Levelsmentioning
confidence: 99%
“…Consequently, the use of intensive electrical fields in direct contact with brain tissue leads to a temperature increase which may have an impact on the conductivity of CSF and other side effects. In fact, recent advances in microfabrication has resulted in very compact microelectrodes which can produce intensive electrical fields with a lower voltage as in the case with recent dielectrophoresis-based devices to monitor neuronal activities [4]. Indeed Honegger et al, showed in their work that it was possible to dynamically control axonal growth in cultured rat hippocampal neurons through the use of AC electrokinetics.…”
Section: Introductionmentioning
confidence: 97%
“…In another flow regime, many devices are meant to apply very low flow rates for long durations. Typical examples of such microfluidic devices are those used for long-term static 5 or perfusion cell culture 6, 7 .…”
Section: Introductionmentioning
confidence: 99%